Recent Publications (Quarterly Journal of Economics, 1946)
Recent Publications Get access The Quarterly Journal of Economics, Volume 60, Issue 3, May 1946, Pages 470–474, https://doi.org/10.1093/qje/60.3.470 Published: 01 May 1946